STRUCTURAL WAYS OF GOVERNING THE INTERNET –THE BRAZILIAN POSITION - Gonet Branco, Pedro Henrique de Moura; Gonet Branco, Paulo Gustavo (Revista Eletrônica Direito e Política, 2020)
The article addresses the peculiarities and complexities of the cyberspace regulation, acknowledging, but not endorsing, the utopic ideal of the cyberspace as a no-law virtual territory. It explores the variety of means of regulating people interconnections around the Globe through the Internet. It points up the need of due heteronomous protection of interests and claims linked to the core proposes of the Internet itself, such as those deriving from the freedom of expression and concerns with the right to privacy. The article takes as standing point Lawrence Lessig’s pathetic dot theory about the four forces that design the use of Internet potentialities. It then focuses on the Brazilian current basic cyberspace normative framework and refers it to Lessig’s theory, mentioning challenges yet to be met. It intends to share the Brazilian experience with the large English speaking auditory, pointing out how Brazilian legal framework relates to mainstream academic approach to Internet regulatory issues. KEYWORDS: cyberspace regulation. Cyberlibertarianism. Pathetic Dot Theory.